Previsão da composição e dos volumes das fases durante a cinética enzimática do biodiesel etílico com lipase líquida utilizando modelo UNIFAC - Nunes, Guilherme Lanfredi Lopes Veronezi (Universidade Federal de São Carlos, 2023)
The production of biodiesel catalyzed by lipases, especially by transesterification of vegetable oils, has been gaining importance in recent decades because it is an efficient and sustainable process. The main differential of this process is the possibility of using low quality raw material, in addition to being a highly energy efficient process compared to the conventional one. Lipases are enzymes that are widely used in the industrial field, as catalysts in the hydrolysis of triacylglycerol, transforming them into glycerol and fatty acids. Additionally, they are capable of catalyzing esterification, transesterification and interesterification reactions. This allows its assignments to be diverse, and can be used in the food, pharmaceutical, cleaning products, water treatment and biodiesel production sectors. During the enzymatic synthesis of biodiesel, using liquid lipase, the reaction occurs at the interface between the polar and non-polar phases. That is, the reaction rate varies as a function of polar and non-polar volumes. Furthermore, the enzyme is soluble only in the polar phase. In this sense, the study of the liquid-liquid equilibrium (LLE) during the enzymatic synthesis of biodiesel is important for a better understanding of this production process. The objective of this research was the development of a model based on liquid-liquid equilibrium that could describe the composition and volume of the phases during the enzymatic reaction of transesterification of soybean oil and ethanol. For this, the UNIFAC group contribution method was applied and variations for biodiesel systems were evaluated. As soybean oil, biodiesel and fatty acids are composed of long chains and their molecular structure depends on their composition, in this work pseudomolecules were elaborated based on the composition of the soybean oil used and on the average molecular structures to define the contribution of each group. Finally, a kinetic model of the reaction developed in the research group, based on the Ping-Pong Bi-Bi mechanism, was combined with the liquid-liquid equilibrium model to improve the knowledge of the polar and non-polar phases during the transesterification reaction.
Composition and volumes prediction of phases during the ethyl biodiesel enzyme kinetics with liquid lipase using the UNIFAC model
Keywords: Biodiesel; UNIFAC; Equilíbrio líquido-líquido; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA